MEMBONGKAR AKAR BIAS GENDER DALAM HUKUM ISLAM (Telaah Fiqh Perempuan Perspektif Sejarah Sosial Hukum Islam) - Asni Asni (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2016)
This article motivated by the proliferation of gender discourse in recent years and the perception of gender bias in Islamic law which is developed over the years. The article discusses the gender bias in Islamic law (fiqh) by analyzing the social history of Islamic law. Based on this analysis, it can be concluded that gender bias in Islamic law is influenced by the condition of socio-cultural time and place, where jurisprudence formulated. Therefore, for the Indonesian context, it takes the efforts of women fiqh development in accordance with contemporary developments and Indonesian culture.